Associations of combined lifestyle behaviors with all-cause and cardiovascular mortality in adults: A population-based cohort study in Jiangxi Province of China - Tao Wang; Tao Wang; Congcong Ding; Congcong Ding; Wei Zhou; Wei Zhou; Lingjuan Zhu; Lingjuan Zhu; Chao Yu; Chao Yu; Xiao Huang; Xiao Huang; et al. (Frontiers Media S.A., 2022)
BackgroundData are limited on the impact of combined lifestyle behaviors on mortality in Jiangxi Province, China.ObjectiveThe study examined the association between combined lifestyle behaviors and all-cause and cardiovascular disease (CVD) mortality in Jiangxi province.MethodsThe baseline survey was completed in Jiangxi Province from November 2013 to August 2014. We conducted a follow-up on 12,608 participants of 35 years of age or older from July 2019 to October 2020. Four known lifestyle behaviors were evaluated: alcohol consumption, smoking, diet (AHEI scores), and physical activity. Cox regression analysis was performed to determine the association of combined lifestyle behaviors with all-cause and CVD mortality.ResultsDuring 65,083 person-years of follow-up, among the 11,622 participants (mean age 59.1 years; 40.1% men) 794 deaths occurred, including 375 deaths from CVD disease in this study. Compared to the favorable lifestyle group, the adjusted HR of all-cause mortality was 1.25 (95% CI, 1.03-1.53) for the intermediate lifestyle group and 1.37 (95% CI, 1.11-1.71) for the unfavorable lifestyle group. Compared to the favorable lifestyle group, the adjusted HR of CVD mortality was 1.50 (95% CI, 1.11-2.03) for the intermediate lifestyle group and 1.58 (95% CI, 1.14-2.20) for the unfavorable lifestyle group. Significant interactions of lifestyle and BMI (P for interaction <0.05) with the risk of all-cause mortality and CVD mortality were observed.ConclusionIn the current study, we reaffirm the associations of combined lifestyle factors with total and CVD mortality in Jiangxi Province, our data suggest that an unfavorable lifestyle was associated with a substantially increased risk of all-cause and CVD mortality.